Prospective study on the impact of BEAM versus FEAM conditioning on occurrence of neutropenic enterocolitis and on transplant outcome in lymphoma patients - Benedetti, Edoardo; Traverso, Ginevra; Pucci, Giulia; Morganti, Riccardo; Bramanti, Emilia; Cavallo, Federica; Capochiani, Enrico; De Maria, Maurizio; Ricchiuto, Vittorio; Stella, Massimo Salvatore; Galimberti, Sara (Frontiers in Oncology, 2024)
Carmustine (BCNU), etoposide, cytarabine, and melphalan (BEAM) is a widely used high dose chemotherapy regimen for autologous stem cell transplantation transplant (ASCT) in lymphoid malignancies. During BCNU shortages, some centers switched to fotemustine-substituted BEAM (FEAM). Neutropenic enterocolitis (NEC) is a life-threatening complication occurring after intestinal mucosa damage related to intensive chemotherapy. NEC mortality may be up to 30-50%. In our study we compared NEC incidence, symptoms, mortality, and transplant outcome in terms of overall survival (OS) and progression free survival (PFS) in the BEAM vs FEAM group. Furthermore, we compared the cost of hospitalization of patients who did vs patients who did not experience a NEC episode (NECe). A total of 191 patients were enrolled in this study (N=129, and N=62 were conditioned with BEAM and FEAM, respectively). All patients received bed-side high resolution ultrasound (US) for NEC diagnosis. NEC incidence, and NEC-related mortality were similar in the BEAM and FEAM group (31 %, and 40.3 %, p= 0.653,and 5 %,and 8%, p=0.627, respectively). At a median follow up of 116 months no difference was noted between BEAM vs FEAM group in terms of OS and PFS ( p=0.181 and p=0.978, respectively). BEAM appeared equivalent to FEAM in terms of NEC incidence, and efficacy. The high incidence of NEC and the low mortality is related to a timely US diagnosis and prompt treatment. US knowledge in NEC diagnosis allows to have comparable days of hospitalization of patients NECpos vs patients NECneg. The cost analysis of NECpos vs NECneg has been also performed.